2018
DOI: 10.1007/s10120-018-0897-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum alkaline phosphatase and lactate dehydrogenase levels in patients with unresectable advanced gastric cancer

Abstract: Background This study evaluated the prognostic value of alkaline phosphatase (ALP) and lactate dehydrogenase (LDH) together with host-related factors in patients with unresectable advanced gastric cancer. Methods The study enrolled 262 patients who received chemotherapy for unresectable advanced gastric cancer at Kochi Medical School from 2007 to 2015. Clinicopathological information and systemic inflammatory response data were analyzed for associations between baseline cancer-related prognostic variables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 30 publications
(44 reference statements)
2
52
0
Order By: Relevance
“…Some studies identified that increased ALP level is correlated with some advanced cancer status. 13,14 Since Chan et al 15 firstly reported the ratio of ALB to ALP combined with ALB and ALP levels can be used as an indicator for predicting the prognosis for patients with liver cancer, and such prediction ability is higher than that based on ALB or ALP levels alone, more studies began to investigate these indicators in other types of cancer. [7][8][9][10][16][17][18][19][20][21] Li et al 16 firstly reported that the relationship between AAPR and OS after investigating 290 stage IV NSCLC patients, finding that AAPR was an independent predictor of OS in multivariate analysis (HR = 0.657, 95% CI = 0.504-0.856, P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identified that increased ALP level is correlated with some advanced cancer status. 13,14 Since Chan et al 15 firstly reported the ratio of ALB to ALP combined with ALB and ALP levels can be used as an indicator for predicting the prognosis for patients with liver cancer, and such prediction ability is higher than that based on ALB or ALP levels alone, more studies began to investigate these indicators in other types of cancer. [7][8][9][10][16][17][18][19][20][21] Li et al 16 firstly reported that the relationship between AAPR and OS after investigating 290 stage IV NSCLC patients, finding that AAPR was an independent predictor of OS in multivariate analysis (HR = 0.657, 95% CI = 0.504-0.856, P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis investigating the prognostic value of the LDH level in solid tumors showed that a high LDH level is associated with poor survival in melanoma, gastric, lung cancer, prostate, and renal cell carcinomas (34). Recently, a high LDH level has been demonstrated to effectively predict the response to cancer treatment, such as chemotherapy (11), anti-angiogenetic agents (35), and checkpoint immunotherapy (22,24) in various cancers. The prognostic role of the LDH level was also investigated in ESCC patients who underwent curative treatment in the study from Wei et al (23).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation process has been proposed to be an important feature in patients with malignant tumors (6), which is involved in the progression of tumorigenesis, disease development, and patient prognosis (7,8). Furthermore, some routinely tested blood parameters, such as neutrophil count, lymphocyte count, and lactate dehydrogenase (LDH) level, have been demonstrated as potential inflammatory biomarkers and have prognostic value in patients with cancers (9)(10)(11). Neutrophils are acknowledged as the first line of defense against inflammations and infections, as well as play an important role in the tumor microenvironment (TME) (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the previous pivotal randomized phase III trials, adjuvant chemotherapy is usually performed after surgery, in order to circulate the anticancer drug(s) throughout the entire body via the bloodstream to control micrometastases and prevent recurrence [4,25,26]. Although postoperative adjuvant chemotherapy is effective in the survival of patients with locally advanced gastric cancer, approximately 20-30% of patients still develop recurrence [19][20][21][22][23][24][25][26][27][28]. The results of the Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer (ACTS-GC) showed the median time from recurrence to death for recurrent gastric cancer patients was 11.4 months [26,28].…”
Section: Discussionmentioning
confidence: 99%